Belarusian compound words and their equivalents in the translations into the German language - Kavalyova, Ina Y. (Journal of the Belarusian State University. Philology, 2024)
The article deals with the compound words selected from the works of Belarusian fiction of the 20th – early 21st centuries and their equivalents found in the texts translated into the German language. The main focus is palced on their structural and semantic features. Overlaps and differences between structural and semantic features are identified, as well as the types of translation patterns are outlined and the degree of their overlap is established. Belarusian compound words and their compound equivalents in German are analysed in view of dividing lexical units into usual (dictionary) and occasional (non-dictionary), both in the source language and in the target language. Translation solutions and quantitative data on structural and semantic translation equivalents are given based on their belonging to usual or occasional units within the identified types.
Keywords: compound word; element of a compound word; usual (dictionary) unit; occasional (non-dictionary) unit; structural and semantic equivalent; complete equivalent; partial equivalent; structural pattern; word meaning